The effect of human resource management practices and innovation: Colombian small and medium-sized enterprises - Salas- Arbeláez, Laura (Cuadernos de Administración, 2020)
The need for small and medium-sized enterprises to innovate and their limited human resource management practices have led to growing research into how the organization’s internal staff-focused characteristics promote a higher degree of innovation. Faced with scarce literature about this relationship in smaller companies in Colombia and the ever-present need to be competitive, this research aims to identify the effect of human resource management practices on innovation in Colombian SMEs. Four hundred and ninety-two surveys were applied to SME managers in Cali, Bogotá, and Medellín to meet such an objective. This research made it evident that human resource management practices affect innovation, but not all practices exert the same influence. Staff selection and performance evaluation affect product innovation, processes, and overall innovation, while compensation only influences product innovation. The other human resource management practices do not account for any kind of effect. This research contributes to prioritizing human resource management practices for innovation and the management thereof within small and medium-sized enterprises.